Effect of Organizational Capabilities on Performance of Micro and Small Family Businesses in Ghana: The Moderating Role of Environmental Characteristics - Osei Bonsu, Samuel (2017)
A thesis submitted to the Department of Marketing and Corporate Strategy of the Kwame Nkrumah University of Science and Technology in partial fulfillment of the award of the degree of Master of Business Administration.